Glimpse on Hemostatic Changes Produced By Plasmapheresis. - Hasan, Zainab M.; Al-Niami, Mayada S.; AL-Shammari, Haider H. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Aphaeresis is a term that means to separate or to take away. The basic idea of aphaeresis is efficient removal of a circulating cellular blood component, either cells (Cytopheresis) or plasma solute (plasmapheresis, plasma exchange).Thus, the treatment goal of aphaeresis is to remove the circulating cell or substance directly responsible for the disease process. Acceleration and development of aphaeresis applications had taken place with the arrival of automated cell separators in 1970s that ensure selectively removal of one or more of blood components from the blood and return the remainder to the individual. Plasmapheresis is separation of plasma from blood cells which are returned to the body. It is accompanied by multiple changes in haemostatic system. As many coagulation factors are removed during procedure, changes in selective parameters: Prothrombin Time (PT), Partial Thromboplastin Time (PTT), Thrombin Time (TT), Fibrinogen (FNG) & platelets count are found when the replacement fluids devoid from coagulation factor are used.Patients and Methods: This clinico-haematological study conducted during a period of six months, from February 2004 to July 2004 at the National Blood Transfusion Center (NBTC) in Baghdad & 50 patients underwent Therapeutic Plasma Exchange (TPE) for various disorders with the use of two types of automated blood cell separators (Haemonetics MCS + which represent an intermittent flow centrifugation technique – IFC & Fresenius AS. TEC 204 which represent the continuous flow centrifugation technique - CFC) in this study, but no instrument type influenced the coagulation screening tests.Results: The changes in all selective parameter: Prothrombin Time (PT), Partial Thromboplastin Time (PTT), Thrombin Time (TT), Fibrinogen (FNG), Platelets count, Haemoglobin (Hb) and Packed Cell Volume (PCV) were significant after Therapeutic Plasma Exchange (TPE). There was no significant difference in changes in crystalloid group from that in Fresh Frozen Plasma group. In crystalloid group, significant correlation was observed between Prothrombin Time (PT), Activated Partial Thromboplastin Time (APTT), Thrombin Time (TT) & volume of Plasma Exchanged (PE) /session, while spacing between sessions and the number of sessions is significantly correlated with Thrombin Time (TT). Plasma fibrinogen concentration and platelets count were decreased in the patients included in our current study.Conclusion: There is no significant difference in changes in haemostatic system whether crystalloid or diluted Fresh Frozen Plasma (FFP) was used as replacement fluid. Thus, crystalloid, solution devoid of coagulation material can be used as a replacement fluid in the Therapeutic Plasma Exchange (TPE) if the volume of Plasma Exchanged (PE) is small. These results are of vital importance from the practical & public health point of view in minimizing the usage of blood components((i.e. Fresh Frozen Plasma (FFP) which is a potential source of Transfusion Transmissible Infections (TTIs) worldwide)) & replaced by crystalloid solution as a safer replacement fluid substitute in Therapeutic Plasma Exchange (TPE) process.